ECONOMIC AND SOCIAL ASPECTS OF RECYCLING: A STUDY APPLIED ON A COOPERATIVE OF COLLECTORS IN VITORIA DA CONQUIST-BA - Santos, Adma Viana [UNESP]; Pires, Elson Luciano Silva [UNESP] (Univ Estadual Paulista Julio Mesquita Filho, 2017)
Given the complexity of waste problem nowadays, recycling has gained wide visibilityin social and environmental discussions. The argument is that there are numerous benefits from the recycling activity. Despite that, it is verified that a large amount of waste generated does not have a destination and correct treatment in most Brazilian municipalities. The objective of this research was to analyze the recycling process as a basis for a profitable production chain, considering mainly the economic and social aspects. Moreover, we explained some of the main discussions regarding the generation and disposal of municipal solid waste, as well as the types of activity and functions of various social actors involved in this productive space circuit. To achieve the proposed objectives, we followed the theoretical guidance and conducted interviews and questionnaires. The survey was applied to 54 cooperated of Recicla Conquista Cooperative (Vitoria da Conquista, Bahia), to representatives of the municipal government, and the main buyers (intermediaries) of the materials from the cooperative, which resulted in the mapping of the routes and destination of production and marketing. Research shows that recycling is effective mainly as an economically viable measure, fact that overlaps the environmental and social aspects. Although the collectorsare the basis of this lucrative process, it was found that theyalso are the least benefited and constitute the precarious and most fragile link in this complex network of relationships.
Keywords: solid waste; Recycling; Economic circuit; Cooperatives; Garbage collection